The art and design of the CRAFT (Commensal Real-time ASKAP Fast Transients) survey - Macquart, Jean-Pierre; Hall, Peter; Clarke, N. (Proceedings of Science, 2010)
We describe the objectives and strategy of a commensal survey for fast (<5s) transient radio sources on ASKAP. Short-timescale transients are associated with the most energetic and brightest single events in the Universe. Our objective is to cover the enormous volume of transients parameter space made available by ASKAP, with an unprecedented combination of sensitivity and field of view. Fast timescale transients open new vistas on the physics of high brightness temperature emission, extreme states of matter and the physics of strong gravitational fields. In addition, the detection of extragalactic objects affords us an entirely new and extremely sensitive probe on the huge reservoir of baryons present in the IGM. We outline here our approach to the considerable challenge involved in detecting fast transients, particularly the development of hardware fast enough to dedisperse and search the ASKAP data stream at real-time rates at high time resolution. CRAFT aims to test of many of the key technologies and survey modes proposed for high time resolution widefield science with the SKA.